Computation of form factors in massless QCD with finite master integrals - von Manteuffel, A; Panzer, E; Schabinger, R (American Physical Society, 2016)
We present the bare one-, two-, and three-loop form factors in massless quantum chromodynamics as linear combinations of finite master integrals. Using symbolic integration, we compute their ε expansions and thereby reproduce all known results with an independent method. Remarkably, in our finite basis, only integrals with a less-than-maximal number of propagators contribute to the cusp anomalous dimensions. We report on indications of this phenomenon at four loops, including the result for a finite, irreducible, twelve-propagator form factor integral. Together with this article, we provide our automated software setup for the computation of finite master integrals.